Uma análise das políticas educacionais para as pessoas com deficiência visual no Estado do Paraná - Zanetti, Patricia da Silva (2017)
The education of visually impaired people presents a conception of deficiency that starts from the naive biological and mystical vision, thus extermination or abandonment, institutionalization, integration and inclusion are the practices that have been adopted in the education of this social segment. This can be seen in the historical study of how blind and low-vision people were treated and educated in primitive societies and in the modes of slave, feudal, and capitalist production that make up the initial part of this research. However, the sociopolitical perspective, whose main exponent, Lev Semenovitch Vygotsky (1896-1934), presents us with aspects about the person with a disability that surpass the determinist visions hitherto preponderant in this field of study. The said theory understands that together with the defect are given the possibilities for its overcoming that occurs through a psychic reorganization that allows the distinct development of the remaining sense organs, leading to a process called supercompensation. The objective of this research is to understand how the State of Paraná has made effective and effective education for people with visual impairment. However, we must place ourselves in the perspective of education that we would like to find in these policies. Principles that guide the conception of education. In this way, historical-critical pedagogy is presented as the pedagogical theory that offers the possibility that the learning can lead to the integral development of these students. In this perspective, it is presented how the education of persons with visual impairment occurred in Brazil and Paraná and, more specifically, how this has occurred since the 1980s of the 20th century in this State. The option for this period is due to the fact that it is in this historical moment that the State of Paraná offered a service to people with visual impairment in the contract, although still based on the integration paradigm, surpassed as a policy only from the year of 2000, from the inclusion paradigm. Thus, through a bibliographical and documentary review, the following documents are presented and analyzed: in the 1980s, Deliberation No. 004/83 - EEC and Deliberation No. 020/86 - EEC; In the 1990s, the document Theoretical-Methodological Foundations for Special Education, 1994; In the 2000s, Deliberation No. 02/03 - CEE and the document Curricular Guidelines of the Special Education for the Construction of Inclusive Curricula of SEED, of 2006. It can be observed that the policy for the education of people with visual impairment remains in the field of conservation of the old welfare practices, segregativas and philanthropic, difficult the process of overcompensation.